Synthesis and Luminescent Properties of Strontium Cerium Oxide Phosphors Doped with Rare Earths - Nannapaneni, P. R. V.; Rao, C. A.; Murthy, K. V. R. (Journal of Scientific Research, 2012)
In this paper we report the synthesis and luminescent properties of Sr2CeO4 doped with rare earths (0.5% concentration of La, Eu and Dy ions) are reported. The powder samples of rare earths doped strontium cerium oxide (Sr2CeO4: La, Eu and Dy ions) was synthesized by a standard solid state reaction method in air at 12000C. These samples were characterized by X-ray diffraction, scanning electron microscope (SEM) and photoluminescence (PL) techniques, particle size analysis. The XRD data revealed that the structure of the Sr2CeO4 as orthorhombic and the calculated average crystallite size is ~10nm. Scanning electron microscopy revealed that the Sr2CeO4 phosphor particles had non-spherical shape and the irregular shaped particles are highly agglomerated. PL excitation and emission spectra of Sr2CeO4 doped with rare earths are recorded at room temperature. The CIE coordinates depicted on 1931 chart of Eu (0.5%) doped Sr2CeO4 shown that the emission colour varies from blue to white. This phosphor has a good potential for application in white light LEDs. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.10965 J. Sci. Res. 5 (1), 1-11 (2013)